Detection of minority point mutations by modified PCR technique: a new approach for a sensitive diagnosis of tumor-progression markers. - Haliassos, A (1989)
The detection of point mutations correlated with diseases, in enzymatically amplified DNA sequences (Polymerase Chain Reaction), is currently performed by digestion of PCR products when an existing restriction site disappears at least in one allele of the amplified mutated sequence or by allele specific radiolabeled probes in all other cases. These methods are the most sensitive but they cannot detect a mutation if it is present in less than 5% of the studied cells. We describe here a method based on the introduction of an artificial restriction site, using a modified primer during the PCR, which creates a RFLP indicative of the studied mutation. This RFLP is detected by a radiolabeled oligonucleotide probe which is not related to the mutation. Our approach multiplies the sensitivity by a factor of 1000 and it is practical for use in screening purposes and the detection, after treatment, of the residual disease in human malignancies. Using this method we detected 20% more mutations at codon 12 in the Ki ras oncogene in DNA from colorectal cancers that were undetectable with all the previous methods.